Tạp chí Khoa học & công nghệ = Journal of science and technology (Trường Đại học Công nghiệp Tp. Hồ Chí Minh, 2021)
Nội dung số này nói về: detection of semantic relations based on knowledge graph, a new hybrid algorithm mpcm for single objective optimization problems, an investigation into the common pronunciation errors made by young learners,...